2016
DOI: 10.1007/s11284-016-1369-4
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of temperature sensitivity of decomposition of soil organic matter along a mountain altitudinal gradient in the Western Carpathians

Abstract: Mountain forest soils contain an important stock of carbon. Their altitudinal gradient can serve as a model for research on the potential risk of increased emission of carbon dioxide to the atmosphere, in a positive feedback of global warming. Using soil samples collected at three elevations (600, 900, and 1200 m a.s.l.) from five separate slopes of the Carpathian Mountains (Poland), we studied the effects of soil physical, chemical and microbial properties controlling the temperature sensitivity (Q10 values) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
7
11
0
Order By: Relevance
“…In the present study, Q 10 values decreased with increasing incubation temperature (Figure ), which was consistent with the observations in numerous individual studies (e.g., Koch et al, ; Hamdi et al, ; Klimek, Jelonkiewicz, & Niklińska, ). Increasing temperature can enhance the size of labile SOC pools by favouring the desorption of SOC–humate complexes and reducing physical protection to accelerate SOC decomposition (Conant et al, ; Davidson & Janssens, ; Schmidt et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, Q 10 values decreased with increasing incubation temperature (Figure ), which was consistent with the observations in numerous individual studies (e.g., Koch et al, ; Hamdi et al, ; Klimek, Jelonkiewicz, & Niklińska, ). Increasing temperature can enhance the size of labile SOC pools by favouring the desorption of SOC–humate complexes and reducing physical protection to accelerate SOC decomposition (Conant et al, ; Davidson & Janssens, ; Schmidt et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, it is generally considered that forest soils at high latitudes are more limited by N than those at low latitudes, so N limitation will stimulate microbes to gain more N from soil organic matter at high temperature according to microbial N mining theory (Chen et al, 2014). Furthermore, long-term microbial adaptation to the el- In the present study, Q 10 values decreased with increasing incubation temperature (Figure 3), which was consistent with the observations in numerous individual studies (e.g., Koch et al, 2007;Hamdi et al, 2013;Klimek, Jelonkiewicz, & Niklińska, 2016).…”
Section: Q 10 In Different Ecosystems and Influencing Factorssupporting
confidence: 91%
“…In that regard, our results confirm the findings from earlier studies that demonstrated the pivotal role of topography (alongside with factors such as vegetation and climate) for the formation of soil organic carbon patterns in high mountain areas [72][73][74]. Spatial variation of organic matter decomposition has been reported to be engendered by differences of soil temperature [75][76][77][78], soil moisture [79][80][81][82], litter quality and quantity [83][84][85], slope processes [86] and seasonality. These factors are likely to be strongly affected by the topographic diversity in our study area, thus they potentially govern also spatial differences that we found in the models of this study.…”
Section: Soil Ecological Implicationssupporting
confidence: 91%
“…Soil organic matter (SOM) decomposition processes are temperature dependent and may accelerate global climate warming through positive feedback (Kirschbaum 2000;Karhu et al 2010;You et al 2019). The temperature sensitivity of soil respiration can be regulated by a range of biotic and abiotic factors (Klimek et al 2016a(Klimek et al , 2020. However, our knowledge in this matter is still far from satisfactory.…”
Section: Introductionmentioning
confidence: 99%